(untitled) (Altre Modernità, 2019)
When we analyse and translate tourist texts promoting or dealing with nonWestern destinations we certainly have to take into account the weight of postcolonial discourses in the representation of these places in the tourist field. Many ex-colonies have become popular tourist destinations, while the detritus of post-colonialism have been transformed into tourist sights, including exotic peoples and customs; artefacts; indigenous lifestyles and cultural heritage (Craik). Therefore, if tourism reinforces postcolonial relationships, tourist texts are deeply embedded in colonial discourses. Some scholars have argued that tourism is a form of “leisure imperialism” and represents “the hedonistic face of neocolonialism” (Crick 322). Hall and Tucker have dedicated a volume to the relation between postcolonial thought and tourism referring back to Edward Said’s seminal work on Orientalism (1978) and to Ashcroft, Griffiths and Tiffin’s The Empire Writes Back (1989), both works which outline the ontological and epistemological distinction that has been made between the Western world and the ‘Other’. Encounters with the non-Western have always provided fuel for myths and mythical language and tourism has developed its own promotional lexicon and repertoire of myths (Selwyn), and as a matter of fact, otherness can be an element that makes a destination worth a visit. Studies have demonstrated how the representation of the ‘Other’ is closely linked to the popularization of accounts of travels and explorations in imperial lands (Pratt; Spurr), and sadly this representation is still part of tourist place promotion (Hall and Page). It is a fact that tourism plays a central role in transforming collective and individual values through ideas of commoditization (Cohen), which implies that what were once cultural displays of living traditions or cultural texts of lived authenticity become cultural products that meet the needs of commercial tourism, as well as the construction of a supposed heritage. Such a situation leads to the invention of traditions and heritage for external consumption that meet visitors’ conceptions of the other (Helu-Thaman; Cronin et al.). A good example of representing a non-Western destination at an international level is the Indian campaign Incredible India launched in 2002 for the European, Asian Saggi/Ensayos/Essais/Essays N. 21 – 05/2019 125 and Middle East markets (Kant). Undertaken by the Government of India to promote India Tourism all over the world, the campaign was released by Ogilvy and Mather India in media print, internet and television. My analysis wants to outline how the main themes of the campaign (yoga, Ayurveda and other spirituality-related concepts, Indian cultures and culinary traditions and festivals all around the country, the cultural heritage and the natural resources) have been developed through time in order to ‘translate’ the uniqueness of India for the Western tourist in the last 15 years. The campaign Incredible India has been developed and renewed over the past few years and is still ongoing. My analysis will follow two stages: in the first I will deal with linguistic and visual techniques that create a determinate idea of India as a tourist destination, in the second I will compare texts in English with their translation into Italian, and specifically the creation of a campaign aimed at Italian tourists.